Investigation of the antioxidant activity and total phenolic content of different Carica papaya plant parts (shoots, leaves, and seeds) extracted using different extraction solvents / Noor Syazreen Mohd Rozy and Muhammad Aidil Ibrahim - Mohd Rozy, Noor Syazreen; Ibrahim, Muhammad Aidil (UiTM Cawangan Negeri Sembilan, 2023)
Carica papaya is an important fruit crop in the tropics and is cultivated for consumption in fresh or processed form and for use in the pharmaceutical, leather, and textile industries. Unlike the papaya fruits that are useful for the food industry, the shoots, leaves, and seeds were often discarded as they are considered waste products without realizing their nutrition potential. This study was conducted to determine the Carica papaya plant part that yields the highest phenolic compound by the Folin- Ciocalteu method and to find out which Carica papaya plant part exhibits the highest antioxidant activity through DPPH free radical scavenging assay. The investigation of antioxidant activity and the total phenolic content of the unused papaya tree parts is significant as the unused parts of the Carica papaya tree like shoots, leaves, and seeds can become potential raw materials for the manufacturing of medicine and drugs. The extraction procedure involved two extraction solvents with different ratios which were methanol, ethanol, and a mixture of methanol and ethanol at 1:1, 1:2, and 2:1 ratio respectively. The methanol-extracted shoots of Carica papaya yielded the highest phenolic compound with 11.70±0.62 mg GAE/g. While methanol-extracted leaves of Carica papaya exhibited the highest antioxidant activity through DPPH free radical scavenging assay with 86.78±0.49%. The present study shows that methanol should be used as the extraction solvent as it is the most efficient solvent in extracting phenolic compounds from the Carica papaya plant's part. Extraction using methanol as the solvent could be used for further studies as it can yield maximum phytochemical compounds from the Carica papaya plant as well as other plant samples.